CGIAR Research Initiative on Diversification in East and Southern Africa: IPSR Innovation Portfolio Management Report - Jacobs-Mata, Inga; Girvetz, Evan Hartunian; Thierfelder, Christian L.; Zulu-Hume, Mercy F.; Joshi, Deepa; Dror, Iddo (CGIAR System Organization, 2022)
The CGIAR Research Initiative on Diversification in East and Southern Africa (Ukama Ustawi) aims to support climate-resilient agriculture and livelihoods in 12 east and southern African countries by helping millions of smallholders intensify, diversify and reduce the risks in maize-based farming through improved extension services, small- and medium-enterprise development, supporting governance frameworks and increased investment with a gender and social inclusion lens. This report provides an overview of the portfolio of innovations developed by the Initiative and its partners.